Visualizing the Maintainability of Feature Models in SPLs - Lima, Luan; Uchôa, Anderson; Bezerra, Carla; Coutinho, Emanuel; Rocha, Lincoln (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM), 2020)
This paper presents data visualizations obtained from the application of 15 measures used to support the maintainability evaluation of Software Product Line (SPL) and Dynamic SPL (DSPL) Feature Models (FMs). To identify these visualizations, we applied a survey to classify a set of 40 measures for evaluating the (D)SPL FMs maintainability. Five visualizations were designed from this classification to analyze the extensibility, static variability, dynamic variability, and structural complexity of the FMs. As result, the experts concluded the designed visualizations assist in FMs maintainability interpretation.